2011
DOI: 10.1109/tbme.2011.2149521
|View full text |Cite
|
Sign up to set email alerts
|

A new measure of movement symmetry in early Parkinson's disease patients using symbolic processing of inertial sensor data

Abstract: Abstract-Movement asymmetry is one of the motor symptoms associated with Parkinson's disease (PD). Therefore, being able to detect and measure movement symmetry is important for monitoring the patient's condition. The present paper introduces a novel symbol based symmetry index calculated from inertial sensor data. The method is explained, evaluated, and compared to six other symmetry measures. These measures were used to determine the symmetry of both upper and lower limbs during walking of 11 early-to-mid-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 28 publications
2
51
0
1
Order By: Relevance
“…Therefore some studies have been focused on atypical motions, like drawing ability (17) and movement symmetry (18,19), which may become a supplementary basis for the early diagnosis of PD. A recent study suggested that a digital pen implanted with the Manus Platform (a novel sensor system) could discriminate early PD patients from control subjects who did not have PD but did have other impairments or PD-like symptoms (such as essential tremor) (17).…”
Section: Diagnosis/early Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore some studies have been focused on atypical motions, like drawing ability (17) and movement symmetry (18,19), which may become a supplementary basis for the early diagnosis of PD. A recent study suggested that a digital pen implanted with the Manus Platform (a novel sensor system) could discriminate early PD patients from control subjects who did not have PD but did have other impairments or PD-like symptoms (such as essential tremor) (17).…”
Section: Diagnosis/early Diagnosismentioning
confidence: 99%
“…Also, early PD patients may exhibit very subtle asymmetrical gait and hand movements (19), which are hard to be observed and evaluated by naked eyes. Therefore, a novel symbol based symmetry index referred to as "SI symb ", which was derived from inertial sensor data, was developed to differentiate between early-to-mid-stage PD patients and healthy controls (18). This novel continuous symbolic symmetry index, SI symb , presented high sensitivity and specificity.…”
Section: Diagnosis/early Diagnosismentioning
confidence: 99%
“…As a result, only the shape of the signal and not its relative temporal characteristics are taken into account. A symbolic method for estimating gait symmetry using accelerometers [24] or gyroscopes [25] has been suggested, which takes into account not only the shape but also the temporal characteristics of the signal. This symmetry measure is used in the present paper.…”
Section: Instrumented Gait Analysismentioning
confidence: 99%
“…The symmetry measure used in this paper was presented in [25]. The sensor signal, accelerometer or gyroscope, was standardized to zero mean and unitary standard deviation, then segmented into N symbols.…”
Section: Instrumented Gait Analysismentioning
confidence: 99%
See 1 more Smart Citation